Presence of exoY, exoS, exoU and exoT genes, antibiotic resistance and biofilm production among Pseudomonas aeruginosa isolates in Northwest Iran - Azimi, Somayeh; Kafil, Hossein Samadi; Baghi, Hossein Bannazadeh; Shokrian, Saeed; Najaf, Khadijeh; Asgharzadeh, Mohammad; Yousefi, Mehdi; Shahrivar, Firooz; Aghazadeh, Mohammad (German Medical Science GMS Publishing House, 2016)
Background: , as Gram-negative rod bacilli, has an important role in human infection. In the present study we aimed to investigate the presence of genes and biofilm production among isolates in Northwest Iran.Material and methods: 160 isolates of were collected and identified by biochemical tests and were characterized for antibiotic resistance. Biofilm production was evaluated by microtiter plate assay and the presence of genes was evaluated by allele-specific PCR (polymerase chain reaction). Chi-square test was used for statistical analysis.Results: The most effective antibiotics against isolates were colistin and polymyxin B. 87% of the isolates were biofilm producers of which 69% were strongly biofilm producers. 55% of the isolates carried , 52% of the isolates carried , and 26.3% and 5% carried and , respectively.Conclusion: Our findings showed different distribution of genes in clinical isolates of in Northwest Iran. and were more prevalent in non-biofilm producers and was more prevalent in biofilm producer isolates. These results might indicate the importance of in biofilm production of .